DINAMIKA MOLEKULER GEN HEMAGLUTININ VIRUS AVIAN INFLUENZA SUBTIPE H5N1 YANG DIISOLASI DARI BERBAGAI SPESIES UNGGAS SEJAK TAHUN 2003 SAMPAI 2008 - , Michael Haryadi Wibowo, drh.,MP.; , Prof. drh. Charles Rangga Tabbu, MSc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Outbreak of avian Influenza (AI) in Indonesia has been reported since the mid of 2003, affected to layer commercial farm in Province of Central and West Java. Clinical sign observation since in the early outbreak in the year 2003 to 2008 indicated some variation of symptoms of AI virus infection. Moreover, the AI infections are still existing in the field sporadically, both in farms with and without AI vaccination practices. This study was a retrospective study which was designed to molecularly characterize of hemagglutinin (HA) gene of AI virus, particularly in the fragment of cleavage site (CS), fusion site (FS), receptor binding site (RBS), and antigenic sites (AS). Avian influenza viruses isolated from various poultry since 2003 until 2008 outbreak in Indonesia, which exhibited variation of symptoms and were obtained from farm with and without AI vaccination practices. Isolation and propagation were done on the chicken embryonated egg specific pathogen free. For virus detection and subtyping, serological identification and reverse transcriptase polymerase chain reaction (RT-PCR) method of H5 and N1 gene fragment was performed. Further characterizations were amplification of CS, FS, RBS, and AS domain of HA gene. All of RT-PCR HA gene positive products were sequenced to determine the nucleotide composition at the targeted fragment. Obtained sequences were analyzed by program Mega 4.0 versions, included multiple alignment, deductive amino acid prediction, phylogenetic tree and pair wise distance calculation. The result showed that all AIV isolates were identified as H5N1 subtype. Sequence analysis of CS area determined five motives of multiple basic amino acids which were classified as highly pathogenic avian influenza virus. The features of the motive were observed have some mutations and deletions. Multiple alignment of FS domain of all viruses isolated since 2003 to 2008 showed a conserved domain. Further characterizations on amino acid responsible for RBS indicated a binding preference to avian like receptor, sialic acid Î± 2, 3 Gal. Antigenic sites analysis determined some mutations of amino acid in certain antigenic sites. Phylogenetic study showed that clustering of AIV did not based on species of bird or geographic origin. Generally, AIV created two clusters of viruses based on years of AIV isolation. Viruses isolated at the beginning of outbreak in the year 2003, 2004, and 2005 tended to cluster which was different from that of isolated from 2006 to 2008. Pair wise distance calculation demonstrated the increase of amino acids substitution were observed at the AIV isolated in the year 2003 to 2008. Chi-square analyses indicated that the lesion type character and vaccination status were not associated with the mutation of HA gene of AIV H5N1 subtype, at CS area, FS, RBS and AS which were studied. Our finding demonstrated that the AIV H5N1 subtype in this study showed molecular dynamics of HA gene and suggests that the AIV H5N1 subtype is evolving continuously.